Unilateral Idiopathic Sensory Trigeminal Nerve Paralysis in a Dog - Dias, Maria Luíza Melo; Mortari, Ana Carolina (Acta Scientiae Veterinariae, 2017)
Background: A spayed-female mixed breed dog was presented due to 2 years reduced visual acuity in the left eye. The investigation revealed corneal melanosis, keratoconjunctivis sicca and loss of facial sensation in the same side. The aim of this report is to describe an unilateral idiopathic sensory trigeminal nerve paralysis and keratitis as consequence of corneal innervation loss was established. Unilateral sensory trigeminal nerve paralysis is a very rare lesion in dogs and causes are unclear. Case: A 5-year-old spayed-female mixed breed dog was presented with a history of two years reduced visual acuity in the left eye. The Schirmer tear test values (without use of topical anesthetic) were 11 and 17 mm/min in the left and right eye respectively. Fluorescein tests were negative for both eyes. All postural reactions and spinal reflexes were normal. Cranial nerve evaluation identified symmetrical facial muscles (temporalis, masseter), indicating no muscle atrophy and normal motor nucleus of the fifth nerve. Absent sensation at the upper and lower lips margins, cornea, eyelids (medial and lateral canthi) and sensation in left nasal side were noted. No palpebral reflex was noticed, but there was spontaneous blinking of eyelids, which indicated normal facial nerve function. All other cranial nerve reflexes including menace response, oculocephalic, and gag reflexes were normal. The owner declined further workup, including cerebrospinal fluid analysis and images studies. According to the clinical presentation and neurological findings, presumptive diagnosis of unilateral idiopathic sensory trigeminal nerve paralysis was established. The dog was observed over 18 months without any clinical improvement. The Schirmer tear test showed same values (12 mm/min) and the melanosis remained unchanged. Discussion: Lesions that affected trigeminal nerve, trigeminal ganglion, or trigeminal tract in the pons and medulla caused facial hypoalgesia or analgesia. The causes of trigeminal nerve damage included neoplasia, trauma, fracture of petrous temporal bone and inflammatory polyneuropathies, but the dog present no signals of these diseases. Trigeminal nerve lesions that affected ophthalmic nerve branch will result in loss of corneal sensation and loss of corneal and palpebral reflex as consequence. Paralysis of this branch cause degenerative changes in the cornea, as neurotrophic keratitis that result in edema and epitelial erosion. The Schirmer tear is the standard test to quantify aqueous tear production and the result (11 mm/min) in dog’s left eye is considered early or subclinical keratoconjunctivis sicca (KCS) sign. The pigmentation results from melanocytic cells migration from the limbal or perilimbal tissues. The keratitis can be active when followed by corneal vascularization, stromal inflammatory cell infiltration and granulation tissue formation. The etiology for idiopathic disease is unknown and isolated sensory trigeminal neuropathy have never been described in dogs. There is no definitive treatment and corticosteroid therapy did not appear to alter the course of the disease in dogs with idiopathic trigeminal neuritis therefore supportive treatment is indicated. The paralysis of trigeminal sensory ophthalmic and maxillary branches can result in corneal alterations.